IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI LEMBAGA PENDIDIKAN ERA SOCIETY 5.0 (STUDI KASUS PADA SEKOLAH MENENGAH ATAS (SMA) BUSTANUL ‘ULUM ANAK TUHA) - Muhammad Latif Nawawi; Wakib Kurniawan; M Abdun Jamil (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Curriculum development is a broad term in education that includes planning, implementation and evaluation. Changes to the school curriculum in Indonesia itself are based on the results of domestic and foreign research related to the learning crisis in Indonesia, one result of which is that many Indonesian children cannot understand simple or straightforward reading and apply accurate concepts and learning. Another observation is that there is a large educational gap between regions and social groups. So, to overcome the crisis with these various challenges requires systemic changes, one of which is through the curriculum, because the curriculum can determine the material used in the learning, the curriculum can also affect the pace and methods of teaching according to the teacher's learning needs. This study aims to describe the Implementation of Merdeka Curriculum in PAI Learning in the Era of Society 5.0 at Bustanul 'Ulum Anak Tuha High School. This research uses a qualitative approach with a case study type. According to Lofland quoted by Lexy J. Moleong, that in qualitative research the main data sources are words and actions, data such as documents and others are called additional data. In this study, researchers obtained data by interview, observation and documentation. Then the data was analyzed by using three techniques, namely: Data condensation, Data Presentation, Conclusion Drawing and data validity testing. The results of the discussion show that the renewal (innovation) method used when learning Islamic Religious Education is to use the Contextual Teaching And Learning (CTL) method or learning strategy. Teachers use several different approaches, strategies, methods and learning techniques in teaching. With this learning model students can more easily understand the material, enjoy learning and develop their critical thinking skills.